Trace elements in the water and fish of tropical watercourses in central Brazil - Roseni da Silva SOUZA; Francisco Leonardo TEJERINA-GARRO; Cleonice ROCHA; Luiz Fabrício ZARA; Affonso Celso GONÇALVES-JUNIOR (Boletim do Instituto de Pesca)
The aim was to compare the trace element concentrations found in samples of water (cadmium, copper, manganese, lead and zinc) from ten water catchments and muscle tissues (aluminum, iron, manganese, lead and zinc) from six fish trophic guilds, both samples collected in watercourses of the Upper Tocantins River, Goiás, Central Brazil. Trace element concentrations did not differ among the water catchments, except for Cu and Mn that exceeded the concentrations allowed by the environmental Brazilian legislation. The highest concentrations (Al, Fe, Mn, Pb e Zn) were found in fish of the guild detritivores, omnivores and terrestrial insectivores, while the aquatic invertivores showed the lowest ones; no correlation was observed between the concentrations of Mn, Pb and Zn of the water samples and fish muscle tissues. It suggests that the hydrological and chemical characteristics of watercourses sampled influence on a similar way the availability of trace elements in the water column. The differences of trace element concentrations observed among the trophic guilds do not display a trend based on fish feed strategy, but on the availability of the trace element in the environment, finding reinforced by the absence of relationship between trace elements concentrations of water and fish muscle tissue.